Strategi Pengelolaan Usaha Jasa Rumah Pemotongan Hewan Ruminansia Secara Berkelanjutan (MANAGEMENT STRATEGY FOR SUSTAINABLE RUMINANT-CATTLE SLAUGHTERHOUSE (RC-S) SERVICES) - Maharani, Maya Dewi Dyah; Sumardjo, Sumardjo; Eriyatno, Eriyatno; Pribadi, Eko Sugeng (Jurnal Veteriner; Vol 18 No 1 (2017)DO - 10.19087/jveteriner.2017.18.1.94, 2017)
Uncontrolled cattle slaughtering may result in reduce water quantity and quality, number of cattle, and product of animal origin that does not fit the criteria of safety-healthy-whole-halal. The research objective was to analyze and measure important variables which might be required in developing a modelas well as to formulate strategic plans for managing sustainable abattoir services. Analysis methods used in this study were: Multidimensional Scaling (MDS) or rap-slaughterhouse, Monte Carlo Analysis, and Analytical Hierarchy Process (AHP). Results of the analysis showed that the important variables were, i.e.: water availability and animal health status (ecological dimension); willingness to conduct hygienic and sanitation procedures at business scale level, service business orientation, availability of animal and slaughtering schedule management (economical dimension); workers safety and security (sociological dimension), noncompliance of the use of infrastructure by managers, workers and service users; lack off ulfillment of the requirements of the building frame (dimension regulations); and processing technology (technological dimension). The priority strategic analysis concluded that supply services of product of animal origin is eligible to be considered as components required in the food security program through the development and renovation program of effective slaughter houses. ABSTRAK Pemotongan hewan yang tidak terkendali mengakibatkan penurunan ketersediaan jumlah dan mutu air, hewan, dan pangan asal ternak yang tidak sesuai kriteria aman-sehat-utuh-halal (ASUH). Tujuan penelitian adalah menganalisis dan mengukur peubah-peubah penting yang diperlukan untuk menyusun model dan merancang rencana strategik pengelolaan usaha jasa rumah pemotongan hewan ruminansia secara berkelanjutan. Metode analisis yang digunakan adalah Multi Dimensional Scaling (MDS) atau rap-slaughterhouse , Monte Carlo, dan Analytical Hierarchy Process . Hasil analisis mendapatkan beberapa faktor-faktor penting, yaitu ketersediaan air bersih dan status kesehatan hewan untuk dimensi ekologi; kesediaan melaksanakan perlakuan yang higienis dan sanitasi pada tingkatan skala usaha; orientasi usaha jasa; ketersediaan hewan; pengaturan jadwal waktu pemotongan untuk dimensi ekonomi; keselamatan dan keamanan pekerja (dimensi sosial); ketidaktaatan penggunaan sarana dan prasarana oleh pengelola, pekerja dan pengguna jasa; kurang dipenuhinya persyaratan rangka bangunan (dimensi peraturan); dan teknologi pengolahan (dimensi teknologi). Strategi prioritas yang dihasilkan adalah pelayanan penyediaan pangan asal ternak layak untuk dijadikan komponen yang wajib dalam program ketahanan pangan melalui program pembangunan dan renovasi rumah pemotongan hewan ruminansia yang efektif.
Keywords: ruminant-cattle slaughterhouse, strategy, Multi Dimensional Scaling Analysis, Monte Carlo analysis, Analytical Hierarchy Process